2014
DOI: 10.1186/1471-2164-15-260
|View full text |Cite
|
Sign up to set email alerts
|

A survey of plant and algal genomes and transcriptomes reveals new insights into the evolution and function of the cellulose synthase superfamily

Abstract: BackgroundEnzymes of the cellulose synthase (CesA) family and CesA-like (Csl) families are responsible for the synthesis of celluloses and hemicelluloses, and thus are of great interest to bioenergy research. We studied the occurrences and phylogenies of CesA/Csl families in diverse plants and algae by comprehensive data mining of 82 genomes and transcriptomes.ResultsWe found that 1) charophytic green algae (CGA) have orthologous genes in CesA, CslC and CslD families; 2) liverwort genes are found in the CesA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 52 publications
6
78
0
Order By: Relevance
“…Genes of the CesA family are supposed to be of the ancient cyanobacteria origin [17,26,29,30]. Results of the phylogenetic analyses showed that in CGA the CesA was a single gene, whereas already in basal land plants CesA formed a single monophyletic group of genes.…”
Section: Cellulose -The Main Component Of Plant Cell Wallmentioning
confidence: 99%
See 4 more Smart Citations
“…Genes of the CesA family are supposed to be of the ancient cyanobacteria origin [17,26,29,30]. Results of the phylogenetic analyses showed that in CGA the CesA was a single gene, whereas already in basal land plants CesA formed a single monophyletic group of genes.…”
Section: Cellulose -The Main Component Of Plant Cell Wallmentioning
confidence: 99%
“…Results of the phylogenetic analyses showed that in CGA the CesA was a single gene, whereas already in basal land plants CesA formed a single monophyletic group of genes. Following, due to the duplication and diversification events, many different CesA subfamilies have evolved in the vascular plants before the divergence of ferns [24,26]. The functions of CesA genes were conserved during the evolution, from the cyanobacterial endosymbiont, by algae ancestors of land plants, to extant groups of Tracheophyta [26,31], indicating the significance of cellulose for development and functioning of all plants.…”
Section: Cellulose -The Main Component Of Plant Cell Wallmentioning
confidence: 99%
See 3 more Smart Citations